Acknowledgment to Reviewers of Pharmacy in 2020 - Pharmacy Editorial Office (MDPI AG, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Pharmacy maintains its standards for the high quality of its published papers [...]